Diode-pumped self-starting Kerr-lens mode locking Nd:YAG laser - Larotonda, Miguel Antonio (2000)
Self-starting Kerr-lens mode locking of a longitudinally, diode pumped Nd:YAG laser is obtained using a piece of glass as the only additional intracavity element. To our knowledge, this is the first Nd:YAG laser operating in these conditions. It is obtained following a design procedure that minimizes the sensitivity on the values of the either fluctuating or poorly known parameters of thermal origin in the laser rod. This procedure is of general interest for KLM lasers. The prototype produces transform-limited pulses of 4.5 ps at a 101.5 MHz repetition rate, with an average output power of 800 mW (at 1064 nm) for a pump power of 3 W (at 808 nm).